Association of Heat Shock Proteins (HSP70), Reactive Oxygen Species and Inflammatory Mediators in Male Infertility - Nuha Yaarub Al-Harbi (Journal of Global Pharma Technology, 2020)
Heat shock protein 70 (HSP70) is considered as a gene which affects semen quality traits. The present study attempted to investigate the relationship between the HSP70 expression level and physiological status in Normozoospermia and an Asthenozoospermi. The current study was planned to investigate the relationship between the HSP70 gene polymorphism and infertility in infertile males with normal sperm parameters. A complete of sixty patients and thirty control subjects were collected between February to May 2019. The genotyping of the HSPA1L gene was performed using polymerase chain reaction (PCR) in addition to restriction fragment length polymorphism (RFLP). We tend to determine vital variations within the genotype frequencies of HSPA1L asthenozoospermia patients and controls. Our results showed highly significant differences between asthenozoospermia patients and control groups in levels TNF, IL-6, and ROS, (p